Anaxiphomorpha hexagona sp. n., a new, unusual swordtail cricket collected from Motuo County, Xizang, China (Orthoptera: Grylloidea: Trigonidiidae: Trigonidiinae) - Ma, Libin (Zootaxa, 2018)
Anaxiphomorpha are rare, small and yellowish swordtail crickets recorded from China and Vietnam. These species are special in their genitalia structure, of which, epiphallus and ectoparamere are armed with multiple lobes or branches. Six species of Anaxiphomorpha are known. The new species, Anaxiphomorpha hexagona, sp. n., possesses antler-like structure of the epiphallus and is described and illustrated.